To run the world the Kremlin's Cold War bid for global power - Radchenko, Sergey (Cambridge University Press, 2024)
What would it feel like To Run the World? The Soviet rulers spent the Cold War trying desperately to find out. In this panoramic new history of the conflict that defined the postwar era, Sergey Radchenko provides an unprecedented deep dive into the psychology of the Kremlin's decision-making. He reveals how the Soviet struggle with the United States and China reflected its irreconcilable ambitions as a self-proclaimed superpower and the leader of global revolution. This tension drove Soviet policies from Stalin's postwar scramble for territory to Khrushchev's reckless overseas adventurism and nuclear brinksmanship, Brezhnev's jockeying for influence in the third world, and Gorbachev's failed attempts to reinvent Moscow's claims to greatness. Perennial insecurities, delusions of grandeur, and desire for recognition propelled Moscow on a headlong quest for global power, with dire consequences and painful legacies that continue to shape our world
2402
Keywords: Ost-West-Konflikt; Außenpolitik; Machtpolitik; Sowjetunion; Periode des Kalten Krieges (ca. 1945 bis ca. 1990); c 1945 to c 2000 (Post-war period); Cold War; General & world history; Geopolitics; Geopolitik; Geschichte allgemein und Weltgeschichte; HIS032020; HIS037100; HISTORY / Military / General; HISTORY / Military / Other; HISTORY / Military / United States; HISTORY / World; Kalte Kriege und Stellvertreterkonflikte; Military history; Militärgeschichte: Nachkriegs-Konflikte; Moderne Kriegsführung; POL054000; POL060000; POL062000; Postwar 20th century history, from c 1945 to c 2000; Soviet Union / Foreign relations / 1945-1991; Soviet Union / Politics and government / 1945-1991